An Enhanced Second-Order Terminal Sliding Mode Control Based on the Super-Twisting Algorithm Applied to a Five-Phase Permanent Magnet Synchronous Generator for a Grid-Connected Wind Energy Conversion System - Ben ouadeh Douara; Abdellah Kouzou; Ahmed Hafaifa; Jose Rodriguez; Mohamed Abdelrahem (Energies)
This paper presents the application of a proposed hybrid control strategy that is designed to enhance the performance and robustness of a grid-connected wind energy conversion system (WECS) using a Five-Phase Permanent Magnet Synchronous Generator (FP-PMSG). The proposed approach combines the second-order terminal sliding mode control technique (SO-STA) with the super-twisting algorithm (STA), with the main goal of benefitting from both their advantages while addressing their limitations. Indeed, the sole application of the SO-STA ensures rapid convergence and robust performances in nonlinear systems, but it leads to chattering and reduces the whole system’s efficiency. Therefore, by incorporating the STA, the obtained hybrid control can mitigate this issue by ensuring smoother control actions and a superior dynamic response. This designed hybrid control strategy improves the adaptability of the control system to wind fluctuations and enhances the system’s robustness against external disturbances and uncertainties, leading to higher reliability and efficiency in the wind energy conversion system. Furthermore, the proposed hybrid control allows optimizing the power extraction and boosting the WECS’s efficiency. It is worth clarifying that, besides this proposed control, a sliding mode controller is used for the grid side converter (GSC) and DC link voltage to ensure stable power transfer to the grid. The obtained simulation results demonstrate the effectiveness of the proposed strategy in improving the stability, robustness, and efficiency of the studied WECS under dynamic conditions, creating a promising solution for control in renewable energy systems operating under severe conditions.